POLITICS OF DEMONETIZATION - Sudhakar; Das, K.Mohan (International Journal of Psychosocial Rehabilitation, 2020)
The word politics includes positives as well as negative opinions. It is regrettable, however, that the use of the word is more negative and that the key explanation behind it is the deterioration of the framework of political meaning. Political leaders and parties indulge in unethical affairs for the sake of political influence and national integration through corruption, black money, forgery, tax fraud and other illegal activities. There are many measures taken to eliminate corruption and black money but those are spreading their arms everywhere. Moreover, the havaladanda, benami properties, money laundering, terrorist activities are unauthorized weapons which threaten the country’s peace and stability. Demonetization is therefore a circumstantial decision taken in November on all those factors. Demonetization, therefore, is a circumstantial decision taken on 8 November 2016 on all of these considerations.